Theoretical-Practical Gap in the Development of Investigative Competencies in Secondary School Teachers (Docentes 2.0 Journal, 2025)
In a constantly evolving educational context, where technological, social, economic, and political changes affect how knowledge is disseminated, it is necessary to develop research skills in teachers to achieve educational quality. This essay aimedto analyze the disconnect between theory and practice in developing research skills in secondary basic education teachers that allow solutions for their integration into teaching processes. This essay was established under the humanistic paradigm, using the deductive method, with a qualitative approach, interpretive type, and narrative topic design. In this sense, aspects associated with research skills were analyzed, such as the disconnection between theory and practice, the role of educational regulations in their formation, models, and approaches for their integration, critical reflection, and continuing education as axes of teacher professional development. It was concluded that only through the integration between theory and practice will it be possible to guarantee the development of research skills that contribute to the transformation of teaching pedagogical practices and the quality of the educational process.
Keywords: Investigative competencies; pedagogical practice; initial training; investigative models